Unveiling Javanese Gamelan influences in Debussy’s Estampes L.100 I. Pagodes: an analytical study - Mohd Zaki Al Hassan, Aisyah Nadiah; Zakaria, Juwairiyah; Mahzair, Ahmad Munir; Ahmad Jamal, Sarah Alia; Badaruddin, Amanina Alwani (College of Creative Arts, 2025)
This study discusses the significant influence of Javanese gamelan music on Claude Debussy's prominent piano work, "Pagodes," from the suite Estampes (L.100). The objectives of this study are; 1) to conduct an in-depth score analysis, and 2) to ascertain the influence of Javanese music on Debussy’s Estampes L.100: I. Pagodes. This study employs a qualitative research design that emphasizes a comprehensive musical analysis of this piece. The comparative analysis was used to juxtapose the results of the score analysis with the established characteristics of Javanese gamelan music’s structural components, harmonic framework, rhythmic complexities, and emotional dimensions of the composition. Finding reveals that elements like pentatonicism, rhythmic patterns, and timbral nuances from Javanese music are intricately integrated into ‘Pagodas. The analysis demonstrates that Debussy also integrates rhythmic principles from Javanese music, including complex polyrhythms, cyclical patterns, and ostinatos. The discovery also demonstrates that Debussy employs the piano's timbral capabilities to evoke the sounds of bonang, metallophones, and gongs. The music texture is a reflection of the structure of gamelan music, with the Gong serving as the structural layer, the Balungan as the core melody layer, and the Panerusan as the elaborating layer. Lastly, Debussy did not simply replicate gamelan music; instead, he abstracted its core principles, such as stratified polyphony, cyclical rhythmic structures, and unique sonorities, to develop an innovative and transformative pianistic language. This research provides musicians and scholars with a refined perspective on one of Debussy's most innovative compositions, while also significantly enhancing the comprehension of the musical exchanges that occurred across diverse cultures in the early 20th century.